SUPERVISION OF ISLAMIC EDUCATION: THE DEVELOPMENT HISTORY OF PESANTREN AMANATUL UMMAH SURABAYA IN IMPROVING THE QUALITY OF PESANTREN EDUCATION - Murtadho, Muhammad Alfa Choirul; Aldiansyah, Muhammad; Shofiyah, Rifdah (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
This article delves into Islamic education supervision with a focus on the development history of Pesantren Amanatul Ummah Surabaya during from 1988 to 2023. Islamic education supervision is a process that aims to improve the quality of education through continuous guidance, supervision and evaluation. This research uses historical research methods consisting of four stages, including; heuristics, verification, interpretation, and historiography. This research concludes that Pesantren Amanatul Ummah Surabaya has successfully developed into a superior Islamic educational institution through commitment to educational quality, innovation, and positive contributions to society, in another sense that Pesantren Amanatul Ummah Surabaya has succeeded in becoming a model of Islamic education that is able to maintain tradition while innovating to face the challenges of modernity. The experiences and strategies applied by this pesantren can be a model for the development of other pesantren in Indonesia. As a result; 1) Pesantren Amanatul Ummah Surabaya was initially founded in 1988 by KH. Asep Saefuddin Chalim, only from the Bina Bangsa school, has gone through a bitter history before becoming the big lodge it is today 2) Pesantren Amanatul Ummah Surabaya is growing rapidly which initially only MTs Unggulan Then followed by MA Unggulan, CI program, Acceleration and many more programs and learning methods in Pesantren Amanatul Ummah Surabaya. 3) Negative and positive responses from the resident close to Pesantren Amanatul Ummah Surabaya.